Financial Inclusion and its Challenges in the Arab Countries: What is the Reality of Algerian Economy? - Ghomari, Souhila; Senoucibereksi, Imene; Zenasni, Soumia (Finance and Business Economies Review, 2022)
Financial inclusion has become, in recent years, a research topic of great importance at the international level. Based on the financial inclusion index adopted by the World Bank, the main objective of this research is to study and analyze the level of financial inclusion in Arab countries compared to the rest of the world, while highlighting its reality in Algeria. The study concluded that Arab countries, and Algeria in particular, still have one of the lowest levels in the world in terms of financial inclusion, despite efforts made to improve and accelerate its levels which have contributed to improve its indicators in recent years.